DEVELOPMENT OF SMART APPS CREATOR-BASED INTERACTIVE LEARNING MEDIA IN ECONOMICS SUBJECT AT SMA NEGERI 2 TENGGARONG - Febri Kerisdianto; Sudarman Sudarman; Ratna Fitri Astuti (Educational Studies: Conference Series, 2022)
This study aims to determine the process of developing interactive media based on Smart Apps Creator in economics for class XI SMA, and to determine students' responses to the media developed. One of the interesting interactive learning media can be developed using the Smart Apps Creator software. In this study, the method used is the Research and Development method. The Research and Development research method is a research method used to produce certain products, and test the effectiveness of these products. The development of this media uses the ADDIE model because it is rational, systematic, easy to learn and complete. The ADDIE model is arranged systematically so that in its implementation it is sequential, each stage that will be passed always refers to the previous stage which goes through a revision or improvement process so that in the next stage an effective learning media product is obtained. The results showed that the material expert validation test scored 4.9, the media expert validation test scored 4.6, small group trials were 86.4%, and group trials were 86.5%. Based on the results of this study, it can be concluded that interactive learning media using Smart Apps Creator is very good and appropriate to use to attract students' interest in learning and make it easier for students to understand economics subject matter.